Pengaruh Fasilitas Terhadap Kepuasan Pengunjung Melalui Keputusan Berkunjung Sebagai Variabel Intervening Pada Objek Wisata Kampoeng Durian Kabupaten Pamekasan - Wulandari, Livia Dwi; As, Fathor (Eco-Entrepreneur, 2023)
This study was undertaken at Kampoeng Durian Tourism, Tebul Timur Village, Pegantenan Subdistrict, Pamekasan Regency. One of the excursions in Pamekasan Regency, Kampoeng Durian Tourism, combines elements of agrotourism and hills. The extant problems are fluctuations or increase and decrease in annual visitors caused by the tour's facilities and infrastructure. This research aimed to determine the effect of facilities on visiting decisions, the effect of facilities on visitor satisfaction, the effect of visiting decisions on visitor satisfaction, and the effect of facilities on visitor satisfaction as an intervening variable. The data was collected through interviews, questionnaire distribution, and literature reviews. In this study, 96 individuals were sampled using a non-probability, non-probability sampling approach and data was analysed using regression and path analysis. The findings of this study indicated that 1) Facilities had a direct effect on visiting decisions. 2) Facilities had a direct effect on visitor satisfaction. 3) visiting decisions had a  direct effect on visitor satisfaction. 4) Facilities had a indirect effect on visitor satisfaction through visiting decisions as an Intervening Variable